Georgia Architectural and Historic Properties Survey of Rural [269] Old Quitman - Madison Highway, Valdosta, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [269] Old Quitman - Madison Highway, Valdosta, Ga. December 1980. Large one story square plan house. Hipped, tin roof. Large hipped dormers. Exposed rafters. Surrounding shed porch with square posts. Clapboard siding. Sash windows with 1/1 lights. Interior chimney. Transom over door. Set on brick piers. Fair condition. Date of Construction: c. 1915. This house is typical of those found in the rural portions of the county.
Georgia Architectural and Historic Properties Survey of Rural [269] Old Quitman - Madison Highway, Valdosta, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.17 MB (1,231,163 bytes).
Keywords: Valdosta (Ga.); Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.)